RELATIONAL MARKETING IN SMALL AND MEDIUM-SIZED ENTERPRISES: CASE OF SMES IN THE PROVINCE OF PICHINCHA - Recalde Rodríguez, María Fernanda; Páez Egüez, Juan Carlos (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
Relational marketing allows to obtain profitable relationships with the customer.   It generates a positive perception of the user towards the brand through a product or service.   This is why a personalized attention that establishes a customer and consumer relationship is needed. The goal is to determine if relational marketing is applied in small and medium enterprises in Pichincha Province. For a company it is more expensive to capture a new customer or recover a lost one than to retain a current one, that is why it is important to determine whether SMEs apply relational marketing or not, its definition, pillars, characteristics and the development of a Relational Marketing Plan. The field work allowed to establish if they manage customer databases, strategies, plans and loyalty programs. It is also important to know if companies take actions to create a value proposition for the customer, and if the customers are always right? In order to know the particularities of this study a descriptive research methodology was used.   The research technique applied was the survey which determined that in 2017 and 2019 only half of companies apply relational marketing, and this is managed empirically by not using a CRM or by not applying the necessary strategies.